Analisis Dan Perancangan Data Warehouse Menggunakan Pendekatan Mixed-Driven (Studi Pada Dinas Komunikasi dan Informatika Kabupaten Sidoarjo) - Qomarul Umam; Satrio Agung Wicaksono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Today technology is possible to help people in their daily activity. Technology also help people in important things. Technology has been implemented by several Organisasi Perangkat Daerah (OPD), there are Badan Perencanaan dan Pembangunan Daerah (BAPPEDA) and Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kabupaten Sidoarjo to conduct reporting. However, the submission of reports carried out still uses On-Line Transaction Processing (OLTP). Therefore, Dinas Komunikasi dan Informatika (DISKOMINFO) Kabupaten Sidoarjo built a data warehouse that is useful for integrating all OLTP data on each OPD, so that the reporting data source becomes centralized and is also useful as OLTP data back-up. The first stage in building a data warehouse is requirements analysis. In this case, requirements analysis data warehouse uses a mixed-driven approach. Based on the results of the requirements analysis, three information packages have been obtained, they are information package budget planning, budget proposal, and budget realization. The information package produced two multidimensional designs in the form of star schema and based on the results of validation testing by conducting expert judgment and verification testing using Requirement Traceability Matrix (RTM) showed that the design that had been made was 100% valid and according to user needs.